Prevalence and Socio-Demographic Association of Depression, Anxiety and Stress Among University Students - S Hishan, Sanil; Jaiprakash, Heethal; Ramakrishnan, Suresh; Mohanraj, Jaiprakash; Shanker, Jayanthi; Boon Keong, Lim (International Journal of Engineering and Technology, 2018)
Prevalence of Stress, anxiety and depression has been identified to be high among university students which may affect their social and professional lives. The study aims at assessing the prevalence of stress, anxiety and depression among university students and analyzes their association with gender, ethnicity and area of upbringing. The study also intends to identify their coping strategies. This was a cross sectional study utilizing validated questionnaires. It was conducted among a total of 143 university students in Johar bahru. The questionnaires used were the socio-demographic questionnaire, DAAS-21 questionnaire and Brief coping strategy Questionnaire. Data was analyzed using SPSS software. Descriptive statistics was used. The mean age of the students under the study was 25.02±8.6 years. Depression was seen in 62.2% of the students and anxiety and stress were seen in 78.3% and 55.9 % students respectively. Depression, anxiety and stress were found more in females than males. Anxiety was more in Malays and depression and stress was more among other ethnic groups. Anxiety and depression were seen more in students with a rural upbringing and stress in students with a urban upbringing. There was no significant association between depression, anxiety, stress and gender, ethnicity and area of upbringing. The mean score for the common coping strategies employed which was acceptance, positive reframing and self distraction were 2.8±0.9, 2.8±1.0, 2.8±1.0 respectively. Prevalence of anxiety was more compared to stress or depression. Students used active coping Strategies to cope with stress.